In vitro rumen fermentation of oil palm frond with addition of Lactobacillus plantarum as probiotic. (November 2019) - Astuti, W D; Fidriyanto, R; Ridwan, R; Rohmatussolihat; Sari, N F; Widyastuti, Y
Abstract: The research evaluated the effects of substitution of elephant grass (EG) with oil palm frond (OPF) and addition of probiotic Lactobacillus plantarum on in vitro rumen fermentation. Treatments were T1: Concentrate 60% + elephant grass 40% + OPF 0%, T2: Concentrate 60% + elephant grass 20% + OPF 20%, T3: Concentrate 60% + elephant grass 0% + OPF 40%, T4: Concentrate 60% + elephant grass 40% + OPF 0% + probiotic, T5: Concentrate 60% + elephant grass 20% + OPF 20% + probiotic, T6: Concentrate 60% + elephant grass 0% + OPF 40% + probiotic. Probiotic increased gas production in each OPF level. Highest gas production from non-probiotic treatments was 99 ml, while highest gas production from probiotic treatments was 124.5 ml. Highest OPF proportion decreased gas production. Highest gas production was resulted from T4 (124.50 ml), higher than T3 (90.63ml). Substitution of EG with OPF decreased methane proportion in probiotic treatments. Highest methane proportion was resulted from T4 (7.31%). Probiotic did not affect digestibility and OPF decreased dry matter and organic matter digestibility. Thus, substitution of EG with OPF decreased gas production and digestibility. Probiotic increased gas production but cannot maintain rumen digestibility as equal as control.